WAKTU KERJA LEMBUR DAN UPAH KERJA LEMBUR DI PERUSAHAAN MENURUT HUKUM POSITIF - Kasino, Yulius (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2007)
ABSTRACT The all perperator of the process production such as worker / labour, labour of union and entrepreneur will be require to coalesce and professionalism of the develop to growing to have free market. The professionalism will be formed if each party is holding responsible each other will rights and obligations specially in wages to labour / worker, don't know of overtime in working fee and also passed to overtime labourage is worker was paid such of daily, one months and also pursuant to set of result. Keywords: labour wages, labour.